Kesepakatan Penetapan Harga Dengan Dasar Penetapan Pemerintah Tentang Tarif Batas Bawah Tiket Pesawat Sebagai Pelanggaran Persaingan Usaha (Studi Putusan Nomor 1811 K/Pdt.Sus-KPPU/2022) - Christian, Yoel (Universitas Ekasakti, 2024)
Every human being needs transportation to be able to move to the destination or place they want to go, because transportation is something that every human being needs, there is a need for regulations that can regulate transportation so that it is not exploited by parties who want to gain excessive profits. Air transportation is a type of transportation that is usually the main choice for traveling long distances, because the time and efficiency are better compared to other transportation. However, if you want to use air transportation, the fare is usually higher compared to other forms of transportation. Because the fare is more expensive, the KPPU as a supervisory institution should be able to control it so that unhealthy business competition does not occur so that consumers using air transportation are not disadvantaged because of the policies implemented. detrimental nature implemented by airlines.